How Wealth Inequality Affects Happiness: The Perspective of Social Comparison - Gao, Lingxi; Sun, Bochi; Du, Ziqing; Lv, Guangming (Frontiers in Psychology, 2022)
Since Easterlin pointed out that economic growth in nations does not guarantee increasing happiness for the average citizen, the underlying reason has remained controversial. The present study focuses on income inequality to explain the “Easterlin Paradox”, ignoring the permanent inequality that long-term wealth accumulation brings. Based on social comparison theory, the literature aims to determine how wealth inequality, which accompanies economic growth, diminishes one’s happiness (inequality aversion). Specifically, we conduct two studies in which we split the wealth inequality into the upward wealth inequality and the downward wealth inequality as measures of upward comparison and downward comparison, respectively. Furthermore, the family life cycle is tested as a moderator. The results indicated that (1) the upward wealth inequality inclination (jealousy effect) is stronger than the downward wealth inequality aversion (proud effect: people enjoy having a superior position in the wealth hierarchy). (2) Family members have the strongest upward inequality aversion in the middle-stage phase of the life cycle (when the family head is approximately 50). The results shed light on how macroeconomics influence changes in individual psychology.